1939
DOI: 10.2307/1363962
|View full text |Cite
|
Sign up to set email alerts
|

Territorial Behavior of the Flammulated Screech Owl

Abstract: I had the good fortune to observe the Flammulated Screech Owl (Otus flammeolus) during the summer of 1938 at two localities, both in the Sequoia National Forest of the Sierra Nevada, in Tulare County, California. The first locality is the vicinity of Whitaker' s Forest (property of The University of California) on the west slope of Redwood Mountain. The life-zone is Transition, consisting of open forest of yellow pine, white fir, incense cedar, and black oak which lies just below the heavy stands of big tree, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…The remarkable crypsis of owl plumage against pine bark may be responsible for the nonrandom use of ponderosa pine as roosting sites in Oregon (Goggans 1986). Marshall (1939) noted that singmg sites were well up in tall trees. used radio-tracking to locate the exact tree s i n p g birds occupied in 22 cases.…”
Section: Roost Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The remarkable crypsis of owl plumage against pine bark may be responsible for the nonrandom use of ponderosa pine as roosting sites in Oregon (Goggans 1986). Marshall (1939) noted that singmg sites were well up in tall trees. used radio-tracking to locate the exact tree s i n p g birds occupied in 22 cases.…”
Section: Roost Sitesmentioning
confidence: 99%
“…Many field guides and compendia now refer to this owl as "locally common." Most authorities (e.g., , Richmond et al 1980, Marcot and Hill 1980 believe that because of its "secretive" habits the flammulated owl simply went undetected in much of its range until ornithologists and birders, following Marshall (1939, began imitating calls to incite vocal responses by territorial males. This procedure enabled collectors to begin an assessment of the U. S. and Middle American range in the 's and 1960's (Marshall 1967) but contributed little to understanding of densities [although up to 10 birds were sometimes called into one location (e.g., Johnson and Russell 1962)l.…”
Section: Estimates Of Local Abundance and Population Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently there was an initial competition for territories among males and later competition among females for obtaining established territorial males as mates. Marshall (1939) observed distinct territorial behavior among males of this species, judging that the territories were relatively small, usually under 300 yards (275 meters) in diameter. He also (1957) reported that in one year there were 18 territorial males in a distance of about 3.6 kilometers surveyed between Sunnyside and the head of Sylvania Canyon of the Huachuca Mountains, Arizo~a, or one territory about every 200 meters of lmear distance.…”
Section: Social Behaviormentioning
confidence: 86%
“…Density estimates are not numerous, but Marshall's (1939) estimates of 24 males in an area of about two square miles suggest an approximate density of about 1.9 males per 40 hectares (4.75 males per square kilometer), and other similar density estimates range from 1 to 5 males per 40 hectares (Reynolds and Linkart, 1987b). Winter (1979) found a density of about 5.3 males per square kilometer in similar California habitat.…”
Section: Habitats and Ecologymentioning
confidence: 97%